COGNITIVE-PRAGMATIC FEATURES OF PHRASEOLOGICAL UNITS (BASED ON SPANISH LANGUAGE MATERIAL) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article examines the peculiarities of phraseological units in the Spanish language. In the article, the cognitive and pragmatic features of intensifying phraseological units, ways of increasing them, the role of the studied units in reflecting the subjective feelings and evaluations of the addresser, as well as methods of optimizing the speech strategy to increase the effect on the receiver are discussed. discussed.